OUTDOOR AIR CONDITIONING - Ezhov, Vladimir Sergeevich; Semicheva, Natalia Evgenievna; Ezhova, Tatyana Vladimirovna; Makhova, Veronica Vitalievna (Journal of Applied Engineering Science, 2017)
The article is devoted to the topical issue of modern cities concerning purification of outdoor air from harmful contaminants of waste gases of thermal power and industrial enterprises, motor vehicles exhaust gases and other sources of air pollution in the most polluted areas of urban transport arteries. Innovative technical solutions based on the applying cheap and affordable adsorbent reducing the concentration of harmful contaminants in outdoor air by means of installing fixed and mobile street air-conditioners in the places with urban motor-vehicle transport congestions are considered.